2016
DOI: 10.1097/phh.0000000000000337
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Workplace Influences on Active Commuting in a Sample of University Employees

Abstract: This study provided insight into institutional influences on AC, indicating that policy, infrastructure, and programmatic initiatives could be used to promote workplace AC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…This could have included incentive programs based on mode choice, health insurance discounts for frequent AT participation, or classes to improve urban biking skills. Other research has shown that employer support for AT is a significant predictor of employee participation, 30,48,54 and creating a "culture" of AT among employees can also lead to social support for AT. 55 Additional campaign strategies could be focused on building social support for AT among coworkers, roommates, family members, and neighbors that are connected to the university.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This could have included incentive programs based on mode choice, health insurance discounts for frequent AT participation, or classes to improve urban biking skills. Other research has shown that employer support for AT is a significant predictor of employee participation, 30,48,54 and creating a "culture" of AT among employees can also lead to social support for AT. 55 Additional campaign strategies could be focused on building social support for AT among coworkers, roommates, family members, and neighbors that are connected to the university.…”
Section: Resultsmentioning
confidence: 99%
“…Additional details on the survey process and other findings from the survey can be found elsewhere. 48 Observations of AT participation. Research technicians observed the number of walkers or bikers onto campus during the last 2 weeks of April 2014 and 2015 according to established protocols.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They are settings of personal growth and exploration for many young adults and help facilitate the development of lifelong health behaviors such as engagement in physical activity (Asadi-Shekari et al, 2014;Dinzeo et al, 2014;Leslie et al, 2011). Due to large campus environments and integrated infrastructure, such as walkways, bikeways, and roadways, students often have access to facilities that promote an active lifestyle within a traditional university setting (Kaczynski et al, 2012;Peachey & Baller, 2015;Sun et al, 2014).The university environment can encourage active behavior for all university members, including students, faculty, and staff (Bopp et al, 2014(Bopp et al, , 2016Sun et al, 2014). However, recent findings have shown an overall decrease in the amount of physical activity reported by both students and faculty throughout most college campuses in the United States…”
mentioning
confidence: 99%
“…The university environment can encourage active behavior for all university members, including students, faculty, and staff (Bopp et al, 2014(Bopp et al, , 2016Sun et al, 2014). However, recent findings have shown an overall decrease in the amount of physical activity reported by both students and faculty throughout most college campuses in the United States…”
mentioning
confidence: 99%